Management indicators of training in agroecological tourism from the Moodle platform - Fernández, Alfonso José (2023)
The Covid-19 pandemic allowed a paradigm shift to all destinations in the world, where the tourism system took advantage of the face-to-face gap in educational institutions or centers, integrating virtual learning teaching environments (VEA) for training in tourism agroecological. This article seeks to disseminate the management indicators of the training in agroecological tourism from the Moodle platform, in turn a qualitative investigation was carried out with the method of systematization of educational experiences, with a descriptive design - field and documentary techniques. In addition, Venturagro Unellez VPDS managed to train 2,518 participants, 70% women and 30% men, using the Moodle platform as a tool for easy access and management, strengthening their knowledge through the EVEA, providing skills and abilities in ICT management. , through training and education in agroecological tourism. In conclusion, agroecological tourism from a perspective of the Moodle platform, generates a synergy between the teacher - participants, through the change from face-to-face teaching planning to an instructional design that is applied to the virtual environments of teaching learning. , which will improve educational content by implementing technological tools such as Moodle as strategies, which presents resources and dynamic activities of easy mastery, where it links a process of construction of activities through socio-community linkage with the three substantive elements of teaching , community and research, generating quality standards in the different formations in the field of agroecological tourism.